2017
DOI: 10.14260/jemds/2017/637
|View full text |Cite
|
Sign up to set email alerts
|

Study of Serum Albumin as a Predictor of Short-Term Functional Outcome in Acute Ischaemic Stroke

Abstract: BACKGROUND Stroke or cerebrovascular accident is a life-threatening neurological disorder comprising more than 50% of admissions in a hospital. Identification of predictors of mortality, especially modifiable ones is vital so that prompt therapeutic measures can be instituted to improve outcome. This study has been undertaken with the intention to determine the association if any between serum albumin and the severity as well as the short-term outcome of acute ischaemic stroke. MATERIALS AND METHODS This obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Most of the patients those who presented with convulsion had poor outcome and expired which is comparable to other studies like Reeta et al and Gaurav et al study. 15,16 Omkar Prasad Baidya et al in their study reported 84% patients with motor weakness which is consistent with this study. 17 Mean age of patients with poor outcome at 1 week postadmission was found to be 68 years in this study which is significant according to statistical analysis.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Most of the patients those who presented with convulsion had poor outcome and expired which is comparable to other studies like Reeta et al and Gaurav et al study. 15,16 Omkar Prasad Baidya et al in their study reported 84% patients with motor weakness which is consistent with this study. 17 Mean age of patients with poor outcome at 1 week postadmission was found to be 68 years in this study which is significant according to statistical analysis.…”
Section: Resultssupporting
confidence: 89%
“…Diabetes mellitus and HTN were the most common risk factors observed in this study which is supported by other studies like Reeta et al, and Gaurav et al, study. 15,16 Most of the patients in this study presented with focal neurological deficit of motor weakness in 85% patients, 18% with slurring of speech, 16% headache,7% head reeling, 9% altered sensorium and 9% with convulsions. Most of the patients those who presented with convulsion had poor outcome and expired which is comparable to other studies like Reeta et al and Gaurav et al study.…”
Section: Resultsmentioning
confidence: 78%
“…A recent study by Babu et al [ 12 ] found that serum albumin has a substantial impact on both the severity and prognosis of strokes. In a later investigation by James et al [ 13 ], researchers found a significant correlation between the levels of serum albumin and the results of rapid functional evaluations. For comparison, these studies did not evaluate blood albumin levels or functional outcomes in the third month.…”
Section: Discussionmentioning
confidence: 99%
“…1 Vascular occlusion of brain artery is caused by thrombo-embolic phenomena. 1,2 Brain ischemia is commoner than brain haemorrhage. Brain ischemic stroke accounts for a large number morbidity form muscle paralysis and also the mortality.…”
Section: Introductionmentioning
confidence: 99%
“…In developing the brain stroke accounts for mortality but ranks as sixth leading cause. 2 Timely institution of drug therapy helps decrease morbidity and mortality and improves the clinical prognosis and patient outcome. Neuroimaging is available one of easy and reliable method of diagnosing the AIS, but it is costly.…”
Section: Introductionmentioning
confidence: 99%